Role of the Court of Justice of the European Union in the Field of Environmental Protection - Tubić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
The rules on environmental protection were quite late included in the founding treaties of the former European Communities. After Single European Act entered into force, there was legal basis for the secondary legislation of the European Community and later European Union. In the practice of the Court of Justice of the European Communities and later Court of Justice of the European Union, the issue of environmental protection has been discussed in several important cases. The Court has established which legal basis is appropriate for enacting regulations and directives related to environment. The case law on relation between the freedom of movement of goods and principle of environmental protection is of special importance because it is necessary to find a balance between these two principles. The judgment in the case of “Danish bottles” is significant because it has confirmed that environmental protection is one of the primary objectives of the Community. Moreover, it has added one obligatory requirement to the list of exceptions from the freedom of movement of goods, which was mentioned in the case Cassis de Dijon. The ECJ has also discussed principles of environmental protection because by developing this area they were established and now have a significant influence on other EU policies.